Mastering Azure Analytics : architecting in the cloud with Azure Data Lake, HDInsight, and Spark - Tejada, Zoiner (Schroff, 2017)
Helps users understand the breadth of Azure services by organizing them into a reference framework they can use when crafting their own big-data analytics solution.